2022
DOI: 10.1039/d1ee03804d
|View full text |Cite|
|
Sign up to set email alerts
|

Mining bitcoins with carbon capture and renewable energy for carbon neutrality across states in the USA

Abstract: Bitcoin mining requires a significant amount of electricity to validate blocks, increasing greenhouse gas emissions. Therefore, major countries such as China, Iran, Russia, Turkey, and Vietnam are banning bitcoin mining...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…To analyze the impact of the proposed HDM model on society, people's livelihood, and the environment, the multi‐dimensional sustainability assessment method of the life cycle proposed in our previous work is adopted. In this method, greenhouse gas emissions (GHG) and fossil energy demand (FED) are integrated into the comparison range of gross domestic product (GDP, USD) generated based on the HDM model 59,60 …”
Section: Methodsmentioning
confidence: 99%
“…To analyze the impact of the proposed HDM model on society, people's livelihood, and the environment, the multi‐dimensional sustainability assessment method of the life cycle proposed in our previous work is adopted. In this method, greenhouse gas emissions (GHG) and fossil energy demand (FED) are integrated into the comparison range of gross domestic product (GDP, USD) generated based on the HDM model 59,60 …”
Section: Methodsmentioning
confidence: 99%
“…48 Analysis of bitcoin mining in the U.S.A indeed showed that states with high penetration of renewables and low electricity prices offer the best economic incentives for miners and initiatives for carbon capture. 49 The increasing need of balancing the electricity production and consumption is one of the biggest challenges of the renewable energy transition. The electrical grid has to operate in a constant balance between the supply and demand to maintain its utility frequency, which is more challenging to achieve with an increasing percentage of intermittent renewable sources.…”
Section: Renewable Energymentioning
confidence: 99%
“…Miners act as “buyers of last resort” in this case, favoring nonrival energy, consumption of which does not reduce supply nor increase prices for other consumers . Analysis of bitcoin mining in the U.S.A indeed showed that states with high penetration of renewables and low electricity prices offer the best economic incentives for miners and initiatives for carbon capture …”
Section: Bitcoin In Greenhouse Gas Emissions and Renewable Energymentioning
confidence: 99%
“…Similarly, it would significantly benefit the development of metaverse industry to study and project such growth in terms of the energy, environment, and climate impacts before the rapidly expanding stage of the metaverse sector. Although the environmental impacts of emerging information and communications technologies (ICTs) and decarbonization technologies have been studied, [16][17][18][19][20][21][22][23][24][25] the advantages and drawbacks of the metaverse on environmental sustainability have only been discussed separately in the media, 26 and no research article has projected the climate impacts of the growing metaverse sector systematically, highlighting the knowledge gap for improving the understanding of how the metaverse boom affects the global climate. To fill the knowledge gap, this study aims to comprehensively investigate the metaverse-induced effects on climate change mitigation, decarbonization, air quality improvement, and energy saving, by incorporating major applications in the metaverse industry and their corresponding physicalworld counterparts.…”
Section: Introductionmentioning
confidence: 99%